Analysis of Human Resource Behavior in Solid Medical Waste Management: Case Study From Regional Public Hospitals Drs. H. Amri Tambunan Deli Serdang, Indonesia - Manurung, Cristo Mori Romario; Delvian, D.; Indirawati, Sri Malem (Manunggal Halim Jaya, 2025)
This research collects and analyzes quantitative data on two research variables: the management of solid medical waste and the behavior (knowledge, attitudes, and actions) of human resources (HR), specifically nurses, environmental health officers, and cleaning service officers. The research population comprised 274 individuals, including nurses, environmental health officers, and cleaning service officers. The sampling technique was purposive, with the inclusion criteria being a work period of more than 2 years. Data was collected through interviews, observations, and document reviews at Drs. H. Amri Tambunan Hospital, Deli Serdang Regency. The data collected was analyzed using frequency distribution with the SPSS 20 application. The results showed that the knowledge of nurses, environmental health officers, and cleaning service officers regarding solid medical waste management was categorized as good (61.1%). The attitudes of these personnel were all in the good category (100%). In comparison, their actions in managing solid medical waste were categorized as good (85%)—the management of solid medical waste at Drs. H. Amri Tambunan Regional General Hospital, Deli Serdang, involves several stages. The reduction and sorting processes still rely on chemical products for cleaning, and the storage at the Temporary Storage Facility (TPS LB3) does not include refrigeration facilities for cases where solid medical waste is stored for more than 2 days after production. Additionally, during transportation, officers are sometimes observed not wearing complete personal protective equipment (PPE) such as helmets, face masks, eye protection, aprons, foot protectors, and gloves. Furthermore, the use of chemical disinfection for waste processing has not received approval from the Environmental Service.